2004
DOI: 10.1177/00343552040470040501
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Ethical Beliefs of Certified Rehabilitation Counselors and National Certified Counselors

Abstract: Results of a national survey of certified rehabilitation counselors (CRCs) are compared with those obtained by Gibson and Pope (1993) from a national sample of national certified counselors (NCCs) to determine their beliefs about whether particular behaviors are ethical, and the degree of consensus or controversy about these behaviors. Commonalities and differences in the beliefs of these two groups are described. Implications for education and the field of rehabilitation counseling are discussed. The authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Court decisions, federal and state laws, and national literature were the least favored. Tarvydas et al (2004) found similar results for the most and least favored sources of ethical information for the top three choices.…”
supporting
confidence: 55%
See 4 more Smart Citations
“…Court decisions, federal and state laws, and national literature were the least favored. Tarvydas et al (2004) found similar results for the most and least favored sources of ethical information for the top three choices.…”
supporting
confidence: 55%
“…In line with the results of Gibson and Pope (1993) and Tarvydas et al (2004) studies, same items in this study were judged predominantly as ethical. Participants in this study similarly judged "Offering or accepting a handshake from a client" and "Addressing client by his or her first name" as overwhelmingly ethical.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations